The analysis of the efficiency of a master-slave parallel algorithm - Čiegis, Raimondas; Šablinskas, Ramūnas (Lietuvos matematikos rinkinys, 1998)
A general master-slave parallel algorithm is described. Three applications are investigated and results of numerical experiments with various clusters of workstations are given. PVM library is used in computations as a message passing interface.